Co-creation Processes Contributing to the Societal Impact of Science: Contributions from the Net4Impact Network - Sandra Girbes; Javier Sebastián; Xosé Pedro Rodríguez; Marta Fontanals; Gerard Campeny; Bruno Gómez; Marta Soler (RIMCIS, 2022)
Meaningful citizen participation throughout the development of research projects has increased the societal impact of science. Co-creation processes promote a more significant societal impact by aligning research with societal needs. In recent years, essential advances in citizen participation in science have been identified. However, there are still critical challenges that limit citizen interaction with scientific creations. This article provides some of the contributions made by the Net4Impact network in the face of these challenges. Specifically, we analyse co-creation processes developed by those projects that have demonstrated societal impact. This qualitative study is based on the analysis of Webinars, meetings with researchers from different scientific areas and Communicative Content Analysis. As a result, this work provides six examples of societal impact in three scientific areas: social sciences, humanities, and engineering. In addition, we analyse the characteristics and implications of the different co-creation processes developed by these successful projects.